NCD and Ageing - Yousef Daoud, Ammar Khaled (International Journal of Human and Health Sciences (IJHHS), 2024)
The trend for many years now worldwide is for the life expectancy of humans to increase in all populations and locations, thus also the proportion of the old-aged. The aging process includes a progressive decline of the powers and faculties of the individuals in all body systems to different degrees and rates of decline until the ultimate stage of death, but can be healthy if it is understood and managed adequately. This decline is rooted at the cellular level by a decreasing ability of cells to regenerate and respond to stresses in the environment. A major characteristic of many Non-Communicable Diseases (like diabetes mellitus, hypertension, hyperlipidemia, and many cancers) is that they show increased prevalence with age, increasing their burden on many individuals, families, and societies’ health sectors, emotionally and financially. The approach to dealing with NCD’s in the aged population is multifaceted, stemming from Islamic religious and ethical foundations, scientific research based and practical solutions. Care should be given for the aged-person in a holistic way taking care of their needs physically (like nutrition, clothing, housing, and medical services availability) and mentally keeping their dignity, autonomy, freedom of harm. Medical management in the elderly poses specific challenges in need for exaggerated side-effects of drugs or dietary supplements used and dangers of polypharmacy which is common. The general Islamic Jurisprudence and behavior like the principles of Taqwa (Fear of Allah Almighty) and Ihsan (Beneficence) that apply for general medical practice are more indicated in taking care of the weak and sick like the elderly by individuals, institutions, and governments. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S16